The Influence of Competence on Satisfaction - Sari, Nur Indah; Jam’an, Andi; Maklassa, Maklassa (Borong Newinera Publisher, 2026)
This study aims to determine the effect of competence, communication on satisfaction and service performance at the Barombong Sub-district Office, Gowa Regency. The method used in this study is a quantitative method with data collection through questionnaires to 52 respondents. The analysis used is PLS-SEM analysis using the SmartPLS application. The results of the respondent description show that most respondents are male (53.84%) and female (46.15%), while respondents are aged 20-35 years (30.76%), 36-50 years (40.38%) and 1-65 years (28.84%). The results of this study indicate that competence has an influence on satisfaction, communication has an influence on satisfaction, competence does not affect service performance, communication does not affect service performance, satisfaction has an influence on service performance, satisfaction can mediate competence on service performance and satisfaction can mediate communication on service performance.